Development of Educational Game Based on Canva Application on Reading Comprehension Skills of Fifth Grade Elementary School Students: Pengembangan Media Game Edukatif Berbasis Aplikasi Canva pada Aspek Keterampilan Membaca Pemahaman Siswa Kelas V Sekolah Dasar - Apriana, Maulidya; Akhir , Muhammad; Adam, Andi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Reading comprehension is a fundamental skill in primary education, influencing students' academic performance across subjects. Specific Background: However, traditional teaching methods often fail to engage students effectively, particularly in Indonesian language classes. Knowledge Gap: Limited use of interactive and technology-based learning media contributes to low reading comprehension outcomes among elementary students. Aims: This study aims to develop and evaluate an educational game based on Canva to enhance reading comprehension skills of grade V students at SDN Sungguminasa V. Results: Utilizing the Borg & Gall development model, the research involved stages from needs analysis to product refinement. The resulting Canva-based educational game was validated by experts with a feasibility score of 97%, showed high practicality with an implementation score of 95.83% and positive teacher feedback (91.66%), and demonstrated strong effectiveness through student responses (99.16%) and significant score improvement from 35.83% (pretest) to 90% (posttest). Novelty: This study presents a novel integration of Canva as a platform for developing subject-specific educational games tailored to primary students’ cognitive levels.Implications: The findings highlight the potential of Canva-based educational games as effective, feasible, and engaging media to support reading comprehension in Indonesian language instruction. Highlights: Enhances student engagement through interactive learning. Significantly improves reading comprehension scores. Validated as highly feasible, practical, and effective. Keywords: Educational Game, Canva, Reading Comprehension, Elementary School